Intelligent assessment of reusable plastic food packaging for a circular supply chain [Abstract] - Mariam Qaiser; Elliot Woolley; James Colwill; Fiona Hatton; Patrick Webb (2023)
Abstract presented at the International Conference on Industry 4.0 for Agri-food Supply Chains: Addressing Socio-Economic and Environmental Challenges in Ukraine, Leicester, UK and Online, 24–25 July 2023.